The World Bank's Perspective on African Higher Education - Teferra, Damtew (International Higher Education, 2009)
In it's report "Accelerating Catch-Up: Tertiary Education in Sub-Saharan Africa", the World Bank places education at the fore of African development priorities. This represents a shift in viewpoint from higher education as luxury to higher education as necessity. While this can be seen as progress, the report still contains gaps in data and may indicate a need for increased attention to this changing sector.